Integrating Teaching Factory Method in ESP Maritime English: Cadets' Perceptions and Implications For Maritime Training - Amiruddin Hadi Wibowo; Akhmad Kasan Gupron; Rohmatul Fitriyah Dewi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: The Teaching Factory (TEFA) method has emerged as a practical approach in ESP Maritime English, particularly in enhancing cadets’ participation in simulated maritime scenarios such as loading and unloading communication, onboard communication checking, and goods tracking via phone. Grounded in experiential learning theory, TEFA bridges the gap between theoretical knowledge and real-world application, preparing cadets for industry demands.Methodology: This study used qualitative case study approach to explore seventh-year maritime cadets’ perceptions of the TEFA method. The subjects were seventh semester maritime cadets from maritime academy. Data collection involved classroom observations and semi-structured interviews, focusing on the cadets’ engagement, confidence, and learning outcomes.Findings: The results showed that 65% of cadets agreed that TEFA made learning Maritime English easier, while 60% found the method enjoyable and engaging. Additionally, 55% of cadets reported reduced anxiety, attributing their increased confidence to the hands-on learning experience provided by TEFA simulations. However, 15% of cadets remained neutral, expressing the need for more structured guidance and additional practice to adapt to the interactive learning approach fully.Conclusion: This study concludes that TEFA effectively bridges the gap between theoretical knowledge and practical maritime communication, making learning more industry relevant. Future research should examine blended learning methods, digital feedback systems, and long-term evaluations to strengthen TEFA’s role in improving cadets’ communication skills and preparedness for maritime operations. Integrating online and practical training can enhance learning flexibility while reinforcing real-world application through virtual simulations. Digital feedback tools can help cadets refining pronunciation and fluency by providing immediate assessments and personalized guidance.Originality: This study addresses a gap in understanding how TEFA influences cadets’ perceptions and learning outcomes in ESP Maritime English, particularly in simulated maritime scenarios. It provides insights into the method’s effectiveness and areas for improvement, offering a foundation for future innovations in maritime education.